New potent antimicrobial peptides from the venom of Polistinae wasps and their analogs - Cerovský, Václav; Slaninová, Jirina; Fucík, Vladimír; Hulacová, Hana; Borovicková, Lenka; Jezek, Rudolf; Bednárová, Lucie (Peptides, 2008)
Four new peptides of the mastoparan family, characterized recently in the venom of three neotropical social wasps collected in the Dominican Republic, Polistes major major, Polistes dorsalis dorsalis and Mischocyttarus phthisicus were synthesized and tested for antimicrobial potency against Bacillus subtilis, Staphylococcus aureus, Escherichia coli (E.c.) and Pseudomonas aeruginosa, and for hemolytic and mast cells degranulation activities. As these peptides possess strong antimicrobial activity (minimal inhibitory concentration (MIC) values against Bacillus subtillis and E.c. in the range of 5-40 microM), we prepared 40 of their analogs to correlate biological activities, especially antimicrobial, with the net positive charge, hydrophobicity, amphipathicity, peptide length, amino acid substitutions at different positions of the peptide chain, N-terminal acylation and C-terminal deamidation. Circular dichroism spectra of the peptides measured in the presence of trifluoroethanol or SDS showed that the peptides might adopt alpha-helical conformation in such anisotropic environments.
Keywords: Antimicrobial Cationic Peptides; Wasp Venoms; Molecular Sequence Data; Wasps; Escherichia coli; Amino Acid Substitution; erytrocyty; Staphylococcus aureus; zvířata; kationické antimikrobiální peptidy; Rats; vosí jedy; antibakteriální látky; Microbial Sensitivity Tests; mastocyty; mikrobiální testy citlivosti; peptidy; Hemolysis; hemolýza; sekvence aminokyselin; Cell Degranulation; inhibiční koncentrace 50; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions; substituce aminokyselin; Bacillus subtilis; sršňovití; krysa rodu Rattus; molekulární sekvence - údaje; Inhibitory Concentration 50; Animals; Amino Acid Sequence; Anti-Bacterial Agents; Erythrocytes; Peptides; Pseudomonas aeruginosa; degranulace buněk; Mast Cells